Student Preference in American VS. British English Accents: A Survey in Non-Native Speakers - Farah Alya Salsabila; Julietta Loviliana; Salma Diva Herlinda Putri (Linguistic, English Education and Art (LEEA) Journal, 2026)
Indonesia is a country that does not use English as its primary language, and accent has emerged as a linguistic factor that influences understanding and the way Indonesian students view their language skills in social and academic contexts. English Accents play a major role in Students learning. Previous studies indicate that students in Indonesia are generally more familiar with and adapted to American accents due to the national education system's incorporation of several American-accented instructional materials. This research employs a qualitative case study design, the qualitative research relies primarily on the collection of the qualitative data. The research is precisely conducted with questionnaires via GoogleForm and interviews. The questions were carefully made and had about 15 items, and the questionnaire (in Google Form format) was given to the 37 students. The students selected to interview were non-native English learners in the age range of 13–18, who have studied and been exposed to English for five to ten years or even more to both American and British English through various media. The findings show a strong preference for American English, mainly by media exposure, perceived ease of understanding and the relevance for global communication.  Students think American English is more modern and useful, while British English seems more formal and prestigious but less used. Although many students learn American English in a formal learning environment, their media consumption further strengthens this preference, students also said that schools should start by teaching one accent like American English, to give a strong base before bringing in other accents. At the end students recognize the functional benefits of both accents, yet more students think that American English is more helpful for their future academic or job prospects. Keywords: Accents, American English, British English, Students’ Preferences, Non-native